The main provisions of the holographic model of the human visual system - Титарь, В. П.; Богданова, Т. В. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”)
Basic principles of holographic model of the human visual system, in which retinal photoreceptors register the diffraction pattern of the observed object as two quadrature components of complex hologram, are considered. The model includes taking the logarithm, spatial filtering and signal averaging on the retina by subtracting the average value of the visual signal. Logarithmic processing quadrature components of hologram in the visual system and getting them information about the observed object are described by means of the complex cepstrum analysis. The results of digital simulations are discussed.